2015
DOI: 10.1177/0040517515581589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oxidized cellulose introduced into ramie fiber by oxidation degumming

Abstract: Oxidized cellulose can be produced from the oxidation reaction of hydrogen peroxide in the degumming process of ramie fibers. In this work, the contents of aldehyde and carboxylate groups in ramie cellulose which occurred during the degumming process were quantitatively determined by the electric conductivity titration method. The morphological changes and chemical components of oxidized cellulose were characterized using SEM, XRD, and FT-IR. Additionally, the relationship between the contents of the oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The crystallinity of L-T fibers, which had inferior peak intensity, was undoubtedly the smallest. This was because the crystallinity is greatly influenced by the cellulose content (Li et al 2015;Meng et al 2016). With a higher cellulose content, the content of non-cellulosic materials, which contained lots of amorphous materials and impurities, is lower (Ebringerová et al 2005), resulting in a larger crystallinity index.…”
Section: Crystal Structure Analysismentioning
confidence: 99%
“…The crystallinity of L-T fibers, which had inferior peak intensity, was undoubtedly the smallest. This was because the crystallinity is greatly influenced by the cellulose content (Li et al 2015;Meng et al 2016). With a higher cellulose content, the content of non-cellulosic materials, which contained lots of amorphous materials and impurities, is lower (Ebringerová et al 2005), resulting in a larger crystallinity index.…”
Section: Crystal Structure Analysismentioning
confidence: 99%
“…NOTE: ORP 12,19 is an important water chemistry parameter and it provides a measurement tool for the oxidizing or reducing capacity of the ambient water. Solutions with stronger oxidation property have a higher ORP value.…”
Section: Effect Of the Mg(oh) 2 Substitution Rate On Ph Value Orp Vamentioning
confidence: 99%
“…Nevertheless, the harsh reaction condition and sophisticated equipment inhibit its further industrial application 9,10 . Therefore, oxidation degumming with alkali hydrogen peroxide presents a valuable and alternative application to focus on, for it requires shorter degumming time and lower degumming temperature 11,12 . However, due to the strong oxidation ability of the peroxides, substantial cellulose degradation may occur during the degumming process, which can cause great damage to fiber properties 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these methods focused on preventing cellulose from degradation, the study on acid groups were seldom studied. Li 14 tried to convert the acid groups in oxidation degummed ramie fiber back to hydroxyl groups by reducing the fiber in NaH 4 B solution, and results showed that this process was very helpful in improving the tensile properties of fiber, However, this important process has not been studied sufficiently yet.…”
Section: · Oh· Ooh· Ohmentioning
confidence: 99%